Performance evaluation of tourism infrastructure in Ciwaluh, Wates Jaya, Cigombong - Hidayah, Ulul; Putri, Erika Pradana; Permana, Mirza; Pamungkas, Guntur Bagus (Optimum: Jurnal Ekonomi dan Pembangunan, 2024)
Kampung Ciwaluh tourism is currently an alternative tourist destination for the people of Bogor and its surroundings. The number of tourist visitors is continually increasing every year. The number of visitors must be increased, including providing adequate tourism facilities. This study aims to assess the performance level of tourism infrastructure in Kampung Ciwaluh based on visitor preferences so that it can become a strong foundation for developing Kampung Ciwaluh Tourism in the future. The research method used to evaluate the level of performance of tourism infrastructure in Kampung Ciwaluh is carried out using Importance and Performance Analysis (IPA). The assessment results of each variable of facilities and infrastructure provide information on the actions that need to be taken to overcome problems in the infrastructure development of Kampung Ciwaluh Tourism. After conducting interviews with 100 respondents, the essential variables in infrastructure development in Kampung Ciwaluh were obtained. However, the condition or level of performance that was still poor was an internet connection. The second priority in improving tourism infrastructure in Kampung Ciwaluh is Clinic/P3K, restaurants, souvenir shops, and scurity posts.